COMPUPERSONS: The Android Within. - Fagan, Edward R. (ETC: A Review of General Semantics)
Focuses on the role of high technology in the future of education and employment. Description of the future of educational instruction according to E. M. Forster in his book "The Machine Stops"; Benefits of computer programming through the science of euthenics; Suggestions in using computers within school curriculum.